The association between single and multiple chronic conditions and depression among older population in India: A comparative study between men and women. (18th October 2021) - Meher, Trupti; Muhammad, Thalil; Gharge, Shivani
Abstract: Objective: The study aimed to estimate the prevalence of depression and to explore the association of specific chronic conditions as well as multi‐morbidity with depression among the older population. Method: The study utilized data from the Longitudinal Ageing Study in India Wave 1 (2017–2018). The total sample size for the present study was 31, 464 older adults aged 60 and above, including 14, 931 males and 16, 533 females. Descriptive statistics along with bivariate and multivariate analyses were performed to fulfil the objectives. Results: The overall prevalence of depression among the elderly population in India was 8.7%. Older women had shown a greater prevalence rate of depression than older men. Among chronic conditions, hypertension, stroke, and bone‐related diseases were found to be significantly associated with depression in the case of both men and women. The prevalence of depression among older adults with three or more chronic conditions was higher in males (14.5%) than in females (11.2%). The association between the number of chronic conditions and depression exhibited a linear trend with an increased odds ratio indicating a higher risk of depression among older adults with multiple chronic conditions. Conclusion: Older individuals with a greater number of chronic illnesses have a higher risk of depression and the risk is proportional to the number of chronic conditions. This signifies the need for the identification of depressive symptoms at an early stage by focussing on the elderly suffering from chronic conditions and educating family members and the community about effective treatments and counselling. Key points: Older women have exhibited a greater prevalence rate of depression than older men Hypertension, stroke, and bone‐related diseases are significantly associated with depression among the older population Older adults with a greater number of chronic conditions have a higher risk of depression, and the risk is proportional to the number of chronic conditions Functional disability is a strong predictor of depression in later life